Penyelesaian Sengketa Kewenangan Lembaga Negara oleh Mahkamah Konstitusi - Luthfi Widagdo Eddyono (The Constitutional Court of the Republic of Indonesia, 2016)
This article is about settlement disputes of authorities of state institutions by the Constitutional Court of Indonesia. Pursuant to Article 24C Paragraph (1) of the 1945 Constitution in conjunction with Article 10 Paragraph (1) of the Constitutional Court Law, the Constitutional Court of Indonesia has the authority to hear at the first and final level, the decision of which shall be final, among others in deciding disputes of authorities of state institutions, the authorities of which are granted by the Constitution. But, the 1945 Constitution and the Constitutional Court Law not provide enough rules for the Constitutional Court to decide the case, especially about objectum litis and subjectum litis.In the Decision Number 004/SKLNIV/2006 dated July 12, 2006 the Constitutional Court using gramatical interpretation (grammatische interpretatie) and declare that to decide upon disputes on authority granted by 1945 Constitution, the first thing to consider is the existence of certain authorities in the Constitution and then to which institutions those authorities are given. Constitutional authority not just textually specified in the 1945 Constitution, but also implicit authority derived from the principal authority, and necessary and proper authority to exercise the principal authority.Related to that, classification of state institutions can be based on the form of power/authority given to the state institution.